2019
DOI: 10.3390/math7111057
|View full text |Cite
|
Sign up to set email alerts
|

Econophysics and Fractional Calculus: Einstein’s Evolution Equation, the Fractal Market Hypothesis, Trend Analysis and Future Price Prediction

Abstract: This paper examines a range of results that can be derived from Einstein’s evolution equation focusing on the effect of introducing a Lévy distribution into the evolution equation. In this context, we examine the derivation (derived exclusively from the evolution equation) of the classical and fractional diffusion equations, the classical and generalised Kolmogorov–Feller equations, the evolution of self-affine stochastic fields through the fractional diffusion equation, the fractional Poisson equation (for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In this section, we discuss the background to Einstein's Evolution Equation, the Random, Efficient, and Fractal Market Hypotheses and the approach to the development of a carbon market future trend indicator. This is a summary only, as this work is detailed more fully in an associated publication by the authors of Reference [36]. Interested readers should refer to this paper for a fuller derivation of the underlying hypothesis and its application to financial markets in general.…”
Section: Stochastic Field Theory and The Determination Of An Investment Indexmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we discuss the background to Einstein's Evolution Equation, the Random, Efficient, and Fractal Market Hypotheses and the approach to the development of a carbon market future trend indicator. This is a summary only, as this work is detailed more fully in an associated publication by the authors of Reference [36]. Interested readers should refer to this paper for a fuller derivation of the underlying hypothesis and its application to financial markets in general.…”
Section: Stochastic Field Theory and The Determination Of An Investment Indexmentioning
confidence: 99%
“…For γ = 2, a Gaussian PDF is obtained; for γ = 1, the PDF is a Cauchy distribution, and, with γ = 0, the PDF is a delta function. Specifically, for r ∈ R 1 , it can be shown that, for γ = 1 [36],…”
Section: The Approach To Predicting Market Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of semi-derivatives and integrals in the mass and heat transfer become an important instant in the field of fractional calculus due to employing the mathematical definitions into physical phenomena [12,13]. In the last decade, using fractional operators which explain the events, situations or modes between two different stages or the phenomena with memory provide more accurate models in many branches of science and engineering including chemistry, biology, biomedical devices, nanotechnology, diffusion, diffraction and economics [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In References [25][26][27][28][29][30][31], the modeling and comparison of the countries and trends in the sense of economics and its parameters are implemented.…”
Section: Introductionmentioning
confidence: 99%